Due to The Law of Property Ownership Certificate (Shm) Site of More Than 5 Plots - Gesang Iswahyudi (Faculty of Law, Merdeka University Surabaya, 2018)
Purpose of this paper is to determine the existence and understand the limitations of property ownership of more than 5 (five ) parcel of land plots relating to the site. State regulating land ownership with the status Certificate of Land Ownership (SHM), where people can only have a maximum of five (5) areas, or the total area of the SHM ownership of no more than 5000 m2 (Five thousand square meters) and That restrictions on land ownership as mandated by Article 7, Article 17 in this case regarding non-agricultural property till now there is no restriction, or no regulation concerning the maximum limit of non-agricultural land property rights. The setting of this case as stated in the Decree of the State Minister of Agrarian Affairs / Head of National Land Agency Number 6 of 1998 on the Granting of Property Rights to Land for House Live. Basic implementation is the treatise consideration plots tread head of BPN RI regulation no. 1 In 2010, dated January 25, 2010. The results of this paper are In order to achieve what is set forth in article 33, paragraph 3 of the Constitution in 1945 the BPN in this case must issue rules concerning restrictions on non-agricultural land property rights more comprehensive and complete in order to prevent and take action if there are groups or parties that accumulate land property rights of non-agricultural, should establish regulations governing the restriction of property rights of non-agricultural formulated-rumusanyang together with the provisions of the restrictions on the land, for example, divide the category of land property rights of non agriculture based strategic area or is not strategic and so that individuals and entities the national land (BPN) to each of limitations of ownership by a person to land his property, so can the implementation of landreform and enacting Law No. 5 of 1960 on Basic Regulation of Agrarian (Basic Agrarian Law) ditelah expected, in relation to the utilization of city planning, site plans is one means of controlling and regulating the use of urban space, and as a driver of regional development optimally, due to site plan contains basic guidelines for area planning, construction planning, area managers, building owners, users or occupant as well as the others associated with the region in preparing and managing a regional part of an operational nature and binding. to resolve this matter roads that can be taken by the owner / individual if you want to file a certificate solution in accordance with his wishes (although more than 5 fields) is to submit a certificate as well as propose the process of solving the tread plots to the National Land Agency (BPN).